Clinical features and immunotherapy outcomes in antibody-negative autoimmune encephalitis: a retrospective case–control study - Gao, Weiwei; She, Jingjing; Su, Lihong; Jin, Shouyue; Yang, Qingwei; Chen, Xingyu; Zhu, Renjing (Frontiers in Neurology, 2024)
Objective This study aimed to compare clinical features, laboratory findings, and immunotherapy responses between antibody-positive and antibody-negative Autoimmune encephalitis (AE) patients. Methods A retrospective analysis of clinical data from 60 AE patients (33 antibody-positive, 27 antibody-negative) diagnosed at Zhongshan Hospital of Xiamen University between January 1, 2016, and March 1, 2024 was conducted. Disease severity and treatment response were assessed using the modified Rankin Scale (mRS) and the Clinical Assessment Scale for Autoimmune Encephalitis (CASE). Results Antibody-positive AE patients more frequently presented with multiple symptoms (≥4 symptoms: 39.4% vs. 14.8%, p = 0.036). They demonstrated significantly elevated serum IgG concentrations (p = 0.010) and cerebrospinal fluid (CSF) leukocyte counts (p = 0.014). Conversely, antibody-negative AE patients presented with higher CSF total protein levels (p = 0.025) and albumin quotients (p = 0.018), indicative of more severe blood–brain barrier disruption. Antibody-positive AE patients more frequently received combination first-line immunotherapy (75.8% vs. 48.1%, p = 0.027) and exhibited superior treatment outcomes (90.9% vs. 70%, p = 0.022). Among critically ill patients (peak mRS score: 4–5), improvement in CASE scores was markedly greater in the antibody-positive cohort (median: 4.50 vs. 1.00, p = 0.024). Conclusion Antibody-positive AE patients manifested a more diverse symptom spectrum, elevated serum IgG concentrations and CSF leukocyte counts, and superior responses to immunotherapy. In contrast, antibody-negative AE patients demonstrated more severe blood–brain barrier dysfunction, as evidenced by higher CSF total protein concentrations and albumin quotients.